Efeitos da suplementação da passiflora incaranata l. sobre a ansiedade em humanos - Silva, Janilson Avelino da Silva (2015)
Anxiety disorders are the most prevalent and economically costly in the context of mental disorders, yet they are among the most commonly underdiagnosed and undertreated. Anxiety in its "natural" way, is considered as a normal emotional reaction in people's lives, serving as protective action, while in his pathological presentation, is characterized by a feeling of persistent concern that hinders the ability of the individual relax . This study aimed to investigate the effects of a single dose and multiple doses (500 mg) of the encapsulated dry extract of the whole plant Passiflora incarnata L. on anxiety in humans. The study is characterized as clinical trial, randomized, double-blind, placebo-controlled. The subjects were randomly assigned to one of the following groups: Placebo or Experimental, n = 30, single dose and placebo or experimental, n = 15, multiple doses. The experimental human anxiety was induced by simulated public speaking test in the following phases: Basal (B), stressful (A), speech 1 (S1), speech 2 (S2) and Final (F); evaluated by through physiological measurements (systolic and diastolic blood pressure, heart rate, Electrical skin conductance and extremities temperature and psychological (State-trait anxiety inventory). In the design of single administration, the physiological and psychological parameters were compared between the placebo and experimental groups by test t (Student) or nonparametric corresponding (Mann-Whitney U). Between phases of each group for these same parameters we used the repeated measures ANOVA of a factor, with post hoc Bonferroni or nonparametric corresponding (Friedman ANOVA) with post hoc Dunn's. We adopted the significance level of 5% (P <0.05). During the single administration in relation to physiological parameters HR was increased in stressful phase (78 ± 3.0 bpm) in the experimental group compared to the placebo group (68 ± 3.0 bpm) (p <0.05), however decreased throughout the speech (92 ± 3.0 to 80 ± 2.0 bpm and 86 ± 2.2 to 74 ± 3.0 bpm, S1 and S2, respectively) in the experimental group compared to the placebo group (p <0.05); 10 psychological measures have not changed. In the design of multiple doses, SBP was reduced in mmHg, in the experimental group compared to the placebo group during all phases. Experimental: 106 ± 1.0 (B) 111 ± 1.0 (A) 121 ± 2.0 (S1) 115 ± 3 (S2) 104 ± 2.0 (F) and Placebo: 121 ± 3 0; 127 ± 3.0; 130 ± 3.0; 130 ± 4.5; 117 ± 3.0 (p <0.05). Between phases in the experimental group there was a reduction in TE in phase F (29.7 ± 0.7 ° C) in relation to the phases A (30.5 ± 0.5 ° C) and S1 (30.6 ± 0 6 ° C). In the experimental group there was a reduction of STAI scores during the second part of speech (42 (39-44 points)) and phase F (41 (40-45 points)) in relation to the baseline phase (45 (42-48 points )). It is suggested that supplementation using Passiflora incarnata L. capsules (500 mg) cardiovascular signals decreased in both single dose and multiple doses, associated with the stress of public speaking.